A phase IV clinical trial of gastrointestinal motility in adult patients with migraine before and after initiation of a calcitonin gene‐related peptide ligand (galcanezumab) or receptor (erenumab) antagonist. Issue 9 (16th September 2022) - Kudrow, David; Nguyen, Linda; Semler, Jack; Stroud, Chad; Samaan, Karen; Hoban, Deirdre B.; Wietecha, Linda; Hsu, Hai‐An; Pearlman, Eric
Abstract: Objective: To compare effects of an initial dose of calcitonin gene‐related peptide (CGRP) monoclonal antibody (mAb) antagonists on gastrointestinal (GI) motility in patients with migraine and to explore if the mechanistic difference contributes to GI adverse events (AEs). Background: Different frequencies of constipation have been observed between CGRP mAbs that target the ligand (galcanezumab [GMB]) or receptor (erenumab [ERE]). Methods: Patients ( n = 65) with migraine without significant GI symptoms were enrolled in a multi‐center, single‐blind phase IV clinical trial (NCT04294147) and randomized 1:1 to receive GMB (240 mg; n = 33) or ERE (140 mg; n = 32). GI whole and regional transit times were assessed using a wireless motility capsule 1 week before and 2 weeks after mAb administration. The primary endpoint was change from baseline in colonic transit time (CTT) within each treatment group. Other measures included GI Symptom Rating Scale (GSRS), Bristol Stool Form Scale (BSFS), and spontaneous bowel movement (SBM) evaluation. AEs were monitored throughout the study. Results: Baseline characteristics indicated significant GI transit time variability with minimal GI reported symptoms. While not statistically significant, a numerical mean increase in CTT was observed in ERE patients ( n = 28, mean [SD] at baseline: 33.8 [29.4] h; least square [LS] mean [SE] change: 5.8 [5.7] h, 95% confidence interval [CI] −5.7 to 17.2, p = 0.320), while GMB decreased CTT ( n = 31, mean [SD] at baseline: 29.3 [24.5] h; LS mean [SE] change: −5.4 [5.4] h, 95% CI −16.2 to 5.5, p = 0.328) compared to baseline. No meaningful changes were observed in other regional transit times. ERE significantly reduced BSFS (LS mean [SE] score −0.5 [0.2], p = 0.004) and SBM (LS mean [SE] −1.2 [0.5], p = 0.0120), and increased GSRS‐constipation compared to baseline (LS mean [SE] score 0.3 [0.1], p = 0.016). GMB increased GSRS‐constipation (LS mean [SE] score 0.4 [0.1], p = 0.002). There were no discontinuations due to or serious AEs. A higher percentage of treatment‐emergent AEs were reported with ERE than GMB (ERE: nine of 32 [28.1%] versus GMB: three of 33 [9.1%]), with constipation the most frequently reported (ERE: five of 32 [15.6%] versus GMB one of 33 [3.0%]). Conclusion: While the primary endpoint of this study was not met, secondary and tertiary endpoints support a within‐ and between‐treatment change in GI effects suggesting possible mechanistic differences between ligand (GMB) and receptor (ERE) antagonism.